GenZ prefers cosmetic brands that are focused on sustainability and environmental issues - Sagar Aman; Jyothi Arul; Ranjith P. V. (BIO Web of Conferences)
The study is conducted to understand the preferences of GenZ and how sustainability influences their purchasing decisions. The study uses primary research to identify the influence of environmental factors on purchasing decisions. The study finds that Generation Z (GenZ) prefers beauty brands that focus on sustainability and environmental issues for several key reasons based on the research: GenZ people are well aware of the environmental issues facing our planet and are committed to preserving and protecting the environment. They are aware of the consequences of their actions and know that the beauty sector has a large impact on the environment. They look for companies that truly care about sustainability and back up their claims with actionable insights. Community reviews and opinions have a great influence on Gen Z customers. They rely on influencers, social media, and online communities to gain knowledge and make wise decisions. Using these opinions and insights, the authors provided suggestions for both brands to attract customers and for consumers to choose brands in the future.